Two new species of Cryptopontius Giesbrecht, 1899 (Copepoda, Siphonostomatoida, Artotrogidae) associated with invertebrates from Northeastern Brazil - Farias, Amilcar; Neves, Elizabeth G.; Johnsson, Rodrigo (Zootaxa, 2020)
Cryptopontius is the most species-rich genus in the family Artotrogidae with 25 species, being recorded in almost all oceans, except in the Arctic. However only three species of this genus have been recorded from the Brazilian coast, all of them along the coast of Pernambuco state. This study describes two new species of the genus. Cryptopontius phyllogorgius sp. nov. differs from other species by having 9-segmented antennule, and nine elements on the third exopodal segment of leg 4. Cryptopontius pentadikos sp. nov. differs from its congeners by having five expressed antennulary segments proximal to fused ancestral IX-XII, two setae on second endopodal segment of leg 1, eight elements on third exopodal segment of leg 1 and the free segment of leg 5 with two setae. A key to species of the genus Cryptopontius is provided.